Aerobic exercise inhibits oxidative stress and improves diabetic cardiomyopathy in rats by activating the PROC/PAR1/Nrf2/HO-1 signaling pathway - Xie, Sicong; Chang, Cheng; Tran, Thi Mai; Zhou, Zhiyi; Yu, Chenshuo; Chen, Yucheng; Lin, Jiayin; Xu, Jiaxuan; Wang, Lei; Zhang, Yang (Frontiers in Physiology, 2026)
Diabetic cardiomyopathy (DCM) is a serious complication of end-stage diabetes that manifests as cardiac hypertrophy and heart failure. The present study performed a bioinformatics analysis to predict possible targets for aerobic exercise to improve DCM, and animal experiments were conducted to detect the relevant mechanisms. Oxidative stress (OS)-DCM-trained differentially expressed genes (DEGs) were retrieved from the GeneCards database and a Gene Expression Omnibus microarray dataset. Subsequently, a protein-protein interaction network was constructed to screen the hub genes of the OS-DCM-trained DEGs. In addition, a model of type 2 diabetes was established using streptozotocin and a high-fat diet. Rats were divided into the control, DCM and DCM plus exercise (DCME) groups. The DCME group underwent 8 weeks of moderate-intensity treadmill training. Assessment of cardiac function, myocardial enzymes and OS-related indicators in each group. Compared with the control group, the levels of BNP, CK-MB, c-TnT, LDH, MDA, LVEF, LVIDd, and LVIDs in the DCM group were significantly increased (P < 0.05), while SOD, GSH, and LVFS were significantly decreased (P < 0.05); The above indicators were significantly improved in DCME group rats (P < 0.05). In addition, the expression levels of target genes predicted to be associated with the aerobic exercise-induced improvement of DCM were detected and western blotting was used to determine the relevant signaling pathways. Bioinformatics analysis identified nine hub genes, which, according to Kyoto Encyclopedia of Genes and Genomes enrichment analysis, were mainly involved in “IL-17 signaling pathway,” “TNF signaling pathway,” “apoptosis” and “necroptosis.” Aerobic exercise improved the heart function and myocardial enzymes of the rats in the DCM group, reduced myocardial damage, and inhibited fibrosis and OS. Detection of the nine core genes revealed that only protein C (PROC) met the predicted trend; PROC expression was lower in the DCM group than that in the control group and was higher in the DCME group than that in the DCM group (P < 0.05). Further confirmation using western blotting suggested that aerobic exercise may improve DCM by activating the PROC/proteinase-activated receptor 1 (PAR1)/nuclear factor (erythroid-derived 2)-like 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway. In conclusion, aerobic exercise may mitigate DCM by activating the PROC/PAR1/Nrf2/HO-1 signaling pathway. These findings could pave the way for further investigations into how exercise might regulate OS and influences DCM progression, providing novel insights into its diagnosis and prognosis.